Peran Mahasiswa Calon Guru MI/SDIT dalam Meningkatkan Kualitas Baca Al-Qur’an pada Mahasiswa Prodi PGMI Universitas Muhammadiyah Riau - Sopiatun Nahwiyah; A. Mualif; Rita Haironi; Ikrima Mailani; Wismanto Wismanto (Departement of Mathematics Education, 2023)
In order to produce professional teacher candidates for public and private Madrasah Ibtidaiyah and the favorite Integrated Islamic Elementary School for PGMI student alumni, a mature strategic plan is needed in order to get maximum results. One of the plans carried out by the PGMI Study Program is to place the outcomes of its students who will become PGMI alumni in the next 4 years, whose place of service needs to be considered. Through the UMRI PGMI FGD which was attended by representatives of the Pekanbaru city ministry of religion, representatives of the Integrated Islamic Elementary School Network (JSIT) and Disdakmen representing MI Muhammadiyah Pekanbaru city. This research was conducted using pure qualitative methods. The findings show that the role of PGMI/SDIT Teacher Candidate Students in Improving the Quality of Reading the Qur'an in PGMI Study Program Students at the University of Muhammadiyah Riau include: (1) Acting as a Demonstrator as well as an Educator. (2) Acting as an Educator with a learning style to peers. (3) Serves as a Mediator and Facilitator. (4) Serve as Evaluator. (5) Playing a role in improving the quality of reading the Koran. By taking on these roles, PGMI students on the tahfizh pathway have directly participated in the success of the final exam fast program because passing tahfizh at least one juz with standard tahsin reading is one of the prerequisites for being allowed to register for the PGMI final exam.